KAJIAN KARAKTERISTIK CURAH HUJAN DI SUB DAS CITARIK, DAS CITARUM JAWA BARAT - Tossin Apandi (Bionatura, 2003)
Rainfall characteristics are important factors in watershed managementplanning. Citarik sub watershed as a part of Citarum watershed is an area beingdeveloped. The objective of this experiment was to study the rainfallcharacteristics at Citarik sub watershed. Survey method was used in thisexperiment, by compiling rainfall data from five rainfall stations in andsurrounding the sub watershed. The results showed that based on depth anddistribution of rainfall, the wet season begins on September until May, and dryseason begins from June to August. The area of rainfall is 1,874 mm/year, withthe number of rainy days is between 88-160 mm/year. Average rainfall intensitywere 34 mm/hour. The frequency of rainfall for 2, 5, 10, 20 and 50 years returnperiods are 103 mm/day, 126 mm/day, 142 mm/day, 162 mm/day and 185mm/day respectively.